The Effect of Oligopolistic Market Structure on the Competitiveness of Agribusiness Msmes in Padang City - Dara Ayu Artika; Zefriyenni Zefriyenni (Jurnal Multidisiplin Sahombu, 2026)
This study aims to analyze the influence of oligopolistic market structure on the competitiveness of agribusiness Micro, Small, and Medium Enterprises (MSMEs) in Padang City. The oligopolistic market structure is characterized by the dominance of a few large business actors who have the ability to influence prices, distribution, and market behavior, thus creating intense competition for MSMEs. The study used a quantitative approach with a survey method. The study population was all agribusiness MSMEs in Padang City operating in the agriculture, livestock, fisheries, and agricultural product processing sectors. The sampling technique used proportional random sampling. Data analysis was performed using simple linear regression with the help of SPSS application. The results of the study indicate that the oligopolistic market structure has a significant influence on the competitiveness of agribusiness MSMEs. Competition from large companies encourages MSMEs to improve innovation, product quality, cost efficiency, and marketing strategies to survive in the market. Therefore, government support is needed through healthy business competition policies, access to financing, marketing digitalization, and increasing human resource capacity to strengthen the competitiveness of agribusiness MSMEs.